Recent Progress of Advanced Composites for Broadband Electromagnetic Wave Absorption - Zhiheng Wei; Zongcheng Li; Dewei Chen; Jin Liang; Jie Kong (Small Structures, 2025)
With the rapid development of radio communication technology, the demand for electromagnetic (EM) wave‐absorbing materials in the fields of stealth technology with strong electromagnet compatibility and high equipment efficiency has increased. The manufacturing processes of existing materials are intricate, and their applicability in extreme weather conditions is limited. The design of multidimensional absorbing materials can effectively address complex application needs, enhance environmental adaptability, and improve both absorption efficiency and wideband performance. To meet the application scope in demanding environments, current EM wave absorption materials must be improved for meeting the requirements of absorptions across multiple frequency bands. Changing the structural design of wave‐absorbing materials is an effective approach to achieving strong, wideband absorption properties and has attracted considerable research attention toward material development. Broadband absorption is conducive to the loss of EM waves at both low and broad frequencies. This study presents design dimensions and outlines the multiscale design strategies for EM wave‐absorbing materials proposed in recent research, including 0D, 1D, 2D, and 3D structural design and optimization. Moreover, this study summarizes the applications of dimensional design strategies for the broadband absorption of EM waves. Finally, the challenges and future trends in the rapid development of broadband microwave absorption are discussed.